A Review of Soil Chemical Properties for Bangladesh Perspective - Md Ashikur Rahman Talukder; Shoma Hore; Ripon Hore (Western European Studies, 2023)
The primary objective of this study is to provide an extensive review of the chemical properties inherent to soil. It is essential to recognize that numerous functions of soil are intricately interlinked with its chemical characteristics. The soil composition within the geographical confines of Bangladesh is notably rich and fertile, contributing to its agricultural productivity and ecological vitality. Delving into the chemical properties of Bangladeshi soil holds substantial potential to enhance our understanding of this dynamic ecosystem, thereby offering valuable insights into factors that influence its fertility, nutrient availability, and overall ecosystem health
Keywords: Extensive overview; interlinked; chemical characteristics